Ultrasonographic and Cytological Analysis of Sub-Involution of Placental Sites in a Bitch: A Case Report - Jena, Dayanidhi Jena; Kadam, Rahul G.; Sakshi (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Sub-involution of the placental site (SIPS) is characterized by presence of abnormally low-resistance widely dilated uteroplacental arteries in the absence of substantial amounts of retained products of conception (Petrovitch, 2009). It is a problem which occurs due to delay in uterine involution and is clinically characterized by continuous sanguineous vaginal discharge after parturition. This is mainly seen in young bitches after first whelping principally due to aberrations in normal healing of maternal endometrium. Although it is quite normal physiologically to have hemorrhagic vaginal discharge after whelping up to 3 weeks, but if it lasts for more than 3 weeks than it is considered as sub-involution of placental sites. However, this discharge can last up to 7-12 weeks post-whelping (Johnston et al., 2001). The primary reason for this sero-sanguinous discharge is excessive invasion of trophoblast cells into deeper layer of uterine tissues even after whelping and voiding of placental tissues. Under normal physiological conditions, it regresses slowly during involution, but in cases leading to SIPS the trophoblast cells penetrate deeper and deeper into maternal endometrium resulting in prolonged sero-sanguinous discharge. In some cases the continuous blood discharge may predispose the animal to anaemic condition which needs to be guarded.